Development Prospect and Preparation Technology of Edible Oil From Microalgae - Xue, Zhaohui; Yu, Yue; Yu, Wancong; Gao, Xin; Zhang, Yixia; Kou, Xiaohong (Frontiers in Marine Science, 2020)
Microalgae are a valuable and rich source of oil. By the means of using microalgae oil as raw materials or additives for edible oil will improve the nutritional and edible value of the latter. This paper compares the lipid content and fatty acid composition of microalgae and traditional oil crops, elaborates the lipid synthesis mechanism of microalgae cells and the strategies of promoting lipid accumulation both from environmental pressure and from molecular pressure, summarizes the methods of breaking microalgae cell walls and extracting oil, analyzes the nutritional value, toxicity, antioxidant, and economic feasibility issues to be considered in microalgae edible oil. It is hoped that this study could provide theoretical basis for the actual production of microalgae edible oil, and provide inspiration for the research on the synthesis, accumulation, extraction and preparation of microalgae oils.